Knowledge, Attitude, and Perception of Youth Population in Indonesia toward COVID-19 Vaccination - Alfian Nurfaizi; Lelyana Sih Afgriyuspita; Ni Made Adnya Suasti; Ummi Imamatal Muttaqin; Berliana Nur Azizah; Indira Syahraya; Baiq Dwi Hadiatul Azni; Ayuning Tetirah Ramadhani; Crysciando Jefryco Putra; Nyilo Purnami (Asian Journal of Health Research, 2023)
Introduction: COVID-19 vaccination acceptance by the youth population is still a major problem. Community vaccination programs are needed to immediately achieve immunity so that the goals of good health and well-being can be achieved. This study aims to identify the factors that influence vaccine acceptance in a group of youth non-health professionals. Methods: This cross-sectional, observational questionnaire-based study was conducted among 194 individuals in the age range of 18 to 25 years through online questionnaires. Data was collected using snowball sampling techniques collect data from respondents about their socio-demographics, knowledge, attitudes, and perceptions (KAP). Statistical used descriptive and analytical calculations (Chi-square and Mann-Whitney test). Results: There was a correlation between occupation, comorbid status, and history of COVID-19 with vaccination acceptance. The average score of knowledge among the non-vaccinated group versus the vaccinated group were 52.13 ± 14.556 and 53.68 ± 13.843 (out of 70), respectively (p= 0.509), while the average score for attitude was 6.76 ± 1.781 and 7.44 ± 1.220 (out of 8) respectively (p = 0.004). The occupation, comorbid status, history of COVID-19, perception of dangerous side effects, and willingness to pay were associated with COVID-19 vaccination acceptance. Conclusion:  The vaccinated group showed a more positive attitude, though their average knowledge score was not significantly different with the unvaccinated group. Massive health promotion regarding COVID-19 vaccine safety, reassuring the population, especially the unemployed population and COVID-19 survivors should be taken by policymakers to ensure adequate knowledge, positive attitudes, and perceptions against COVID-19 vaccination.